2013
DOI: 10.1063/1.4829899
|View full text |Cite
|
Sign up to set email alerts
|

Solvent dependent branching between C-I and C-Br bond cleavage following 266 nm excitation of CH2BrI

Abstract: It is well known that ultraviolet photoexcitation of halomethanes results in halogen-carbon bond cleavage. Each halogen-carbon bond has a dominant ultraviolet (UV) absorption that promotes an electron from a nonbonding halogen orbital (nX) to a carbon-halogen antibonding orbital (σ*C-X). UV absorption into specific transitions in the gas phase results primarily in selective cleavage of the corresponding carbon-halogen bond. In the present work, broadband ultrafast UV-visible transient absorption studies of CH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
(173 reference statements)
1
10
0
Order By: Relevance
“…The rise in the concentration of CH 2 I-Br roughly correlates with a depletion of CH 2 Br-I, suggesting a conversion from CH 2 Br-I to CH 2 I-Br. This conversion was earlier found by Anderson et al 83 supporting the hypothesis of isomer conversion at our experimental conditions. This allows us to further incorporate the conversion rate into the fitting.…”
Section: A Kinetics Of Photoproduct Species In Cyclohexanesupporting
confidence: 93%
See 4 more Smart Citations
“…The rise in the concentration of CH 2 I-Br roughly correlates with a depletion of CH 2 Br-I, suggesting a conversion from CH 2 Br-I to CH 2 I-Br. This conversion was earlier found by Anderson et al 83 supporting the hypothesis of isomer conversion at our experimental conditions. This allows us to further incorporate the conversion rate into the fitting.…”
Section: A Kinetics Of Photoproduct Species In Cyclohexanesupporting
confidence: 93%
“…Such behavior is influenced by the different polarities of the solvents. 83 Results of six Gaussians' fitting (not reported here) clearly show no contribution of the B-band, neither in cyclohexane nor in methanol, at the wavelength of λ = 267 nm. It can be concluded that the formation of the CH 2 I-Br in the solvent cage just after the UV photodissociation is unlikely.…”
Section: B Absorption Spectroscopy On Ch 2 Ibrmentioning
confidence: 68%
See 3 more Smart Citations